FACTORS INFLUENCING PURCHASE INTENTION TOWARD HALAL COSMETICS - Rosida, Rida (Universitas Airlangga, 2018)
Nowadays, more and more people are aware of the existence of halal products, especially among Muslim consumers. Halal products are increasingly in demand, ranging from food, financial and non-financial products, to tourism and health products. This has encouraged manufacturers engaged in food, cosmetics, and pharmaceutical products to develop strategies to market their products. The purpose of this study is to analyze the influence of factors such as brand, price, quality, and labeling on the intention to purchase halal cosmetics. The population in this study was Muslim women residing in West Java. The sampling technique used was purposive sampling-quota sampling with a sample size of 106 people. The method used in this study is the causality method with a quantitative approach. The data analysis technique used is multiple linear regression. The results show that of the four independent variables, only three variables have a significant effect on the intention to purchase halal cosmetics, namely: brand, price, and labeling. Meanwhile, quality does not have a significant effect. Simultaneously, all X variables (brand, price, quality, and labeling) influence the intention to purchase halal cosmetics. Keywords: Brand, Price, Quality, Labeling, Intention, Halal Cosmetics